Dietary pesticide exposure profiles in the NutriNet-Santé cohort. (13th November 2019) - Rebouillat, P; Vidal, R; Cravedi, J-P; Debrauwer, L; Gamet-Payrastre, L; Touvier, M; Hercberg, S; Lairon, D; Baudry, J; Kesse-Guyot, E
Abstract: : Pesticides are commonly used in current agriculture and some negative effects are suspected for human health but evidence from dietary exposure in the general population is lacking. This study aimed to describe dietary pesticide exposure among French cohort participants. Organic and conventional food consumption was assessed using a self-administered semi-quantitative food frequency questionnaire in 2014 in the NutriNet-Santé cohort. Exposure to 25 commonly used pesticides was estimated using contamination data (CVUA Stuttgart) accounting for farming system. Dietary pesticide exposure profiles were identified using Non-negative Matrix Factorization, adapted for non-negative sparse data and then introduced in a hierarchical clustering process. The 6 identified clusters (n = 34, 193) seemed to be exposed to the same molecules with gradual intensity. Cluster 1 was characterized by the lowest energy-intake and dietary pesticide exposure, and high consumption of organic food groups (23.3%). Proportion of male participants was higher than in other groups. Clusters 2 and 5 were characterized by intermediate energy intake, lower organic food consumption and intermediate pesticide exposure. High conventional fruits and vegetables intake and high pesticide exposure were observed in cluster 3, composed of a lower smokers' proportion. Cluster 6 was characterized by the highest energy intake, lowest organic food consumption (9%), and highest pesticide exposure; high consumption levels of conventional fruits, vegetables and a higher proportion of vegans were observed. For cluster 4, pesticide exposure varied more across molecules than for other clusters. The highest exposures were observed for Acetamiprid, Azadirachtin, Cypermethrin, Pyrethrins, Spinosad pesticides. Proportion of organic food in the diet was the highest (31.5%). Dietary pesticide exposures seem to vary across the clusters and related to the proportion of organic food in the diet. Key messages: Dietary pesticide exposures seemed to vary gradually across the clusters and depending on the proportion of organic food in the diet. High consumers of conventional FV in this cohort seem to be more exposed to our selection of pesticides.